Covert collection of information on the preparation and commission of crimes under contemporary conditions - Tuz, O.S.; Matnyak, V.M. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The article provides a comprehensive analysis of modern approaches to covert information acquisition concerning the preparation and commission of crimes in the context of Ukraine is evolving security environment. It outlines the legal, organizational, and technological foundations for conducting covert investigative (search) actions (CISAs), which remain one of the key instruments of law enforcement agencies in preventing, detecting, and documenting criminal offenses. The article reviews the provisions of the Criminal Procedure Code of Ukraine and the Law «On Operative and Investigative Activity», which regulate the authorization procedures, time limits, and conditions for applying covert methods [1–3]. The jurisprudence of the Supreme Court of Ukraine is examined, defining the admissibility of evidence obtained through such actions [4–7]. Special attention is devoted to the practice of the European Court of Human Rights, which emphasizes the principle of proportionality between national security needs and individuals’ right to privacy [8–11]. The research highlights that the effectiveness of CISAs largely depends on combining human intelligence, technical surveillance, and international cooperation. The experience of joint operations between Ukraine, Poland, and Lithuania demonstrates the value of coordinated efforts in countering transnational crime, illegal migration, and arms smuggling [14–15]. The article identifies ways to improve legal regulation, internal control, personnel training, and the use of innovative technologies such as OSINT and artificial intelligence. The purpose of this study is to identify current trends and challenges in implementing covert investigative actions in Ukrainian law enforcement practice and to propose measures to enhance their effectiveness while ensuring respect for human rights. The scientific novelty lies in integrating legal and technological approaches to assessing covert operations within the framework of national security. The practical significance of the results lies in their potential to strengthen legislation, improve interagency coordination, and promote European standards of legality and human rights protection in the field of covert intelligence collection.